Extracellular degradation of lipoprotein lipase in rat adipose tissue - Wu, Gengshu (BioMed Central, 2005)
BACKGROUND: Recent studies in vivo indicate that short-term regulation of lipoprotein lipase (LPL) in rat adipose tissue is post-translational and occurs by a shift of the lipase protein towards an inactive form under the influence of another gene with short-lived message and product. It has not been possible to reproduce this process with isolated adipocytes suggesting that other cells are needed, and perhaps mediate the regulation. The objective of the present study was, therefore, to explore if explants of adipose tissue could be used for studies of the regulatory process. RESULTS: When explants of rat epididymal adipose tissue were incubated, LPL mass and activity decreased rapidly. Mass and activity within adipocytes remained constant for at least six hours, demonstrating that it was the extracellular portion of the enzyme that decreased. Adipocytes isolated from the explants after three or six hours of incubation retained their ability to secrete LPL to the medium. Addition of a cocktail of protease inhibitors to the incubation medium slowed down the decrease of LPL mass. Chloroquine was without effect, indicating that the degradation was not lysosomal. (125)I-labeled LPL added to the medium was degraded to acid soluble products, indicating that the degradation occurred extracellularly. Fragmentation of the labelled lipase occurred in conditioned medium and this process was virtually abolished by two MMP inhibitors. CONCLUSIONS: The decrease of LPL mass and activity that occurs when explants of rat adipose tissue are incubated is due to proteolysis of extracellular LPL. The adipocytes continue to produce and secrete the enzyme. The effect of inhibitors indicates, but does not prove, that the degradation is mediated by MMPs. It appears that this process is accelerated in the tissue fragments compared to intact tissue.